Marketing social : a otica, a etica e sua contribuição para o desenvolvimento da sociedade brasileira - Gonçalves, Lopes (1991)
Marketing as a social product, has been created, raised and spread alI over the world mainly as a tool to serve private, micro-economic, l?rofit, short run interests. Over the last twenty years,a steadly growing trend has been noticed in this field,due to the evidences that marketing has not delivered what it had promissed: society's needs fullfillment. Several American theorists and practioners marketino and non marketing specialists - are considered to have contributed to this evaluation of the marketing concept which has led to consolidate new 'sub-disciolines' in the core o f marketing, name ly: 'non business' (not for profi ti non orofit organizations, public services, government) 'political candidates', 'health, education, social services'; 'ideas and social causes' marketing. This paper deals with the latter marketing subdiscipline , that applied to social causes and i ts oocasional contributions to Brazilian socio-economic development, considering both marketing and moral/ethical frameworks. The work suggests that are, have been and will be several possibilities of applying social marketing as a planning and implementing tool for both theorists and practioners of administration.